A Fast Algorithm for Solving a Class of the Linear Complementarity Problem in a Finite Number of Steps - Yamna Achik; Asmaa Idmbarek; Hajar Nafia; Imane Agmour; Youssef El foutayeni (Abstract and Applied Analysis)
The linear complementarity problem is receiving a lot of attention and has been studied extensively. Recently, El foutayeni et al. have contributed many works that aim to solve this mysterious problem. However, many results exist and give good approximations of the linear complementarity problem solutions. The major drawback of many existing methods resides in the fact that, for large systems, they require a large number of operations during each iteration; also, they consume large amounts of memory and computation time. This is the reason which drives us to create an algorithm with a finite number of steps to solve this kind of problem with a reduced number of iterations compared to existing methods. In addition, we consider a new class of matrices called the E-matrix.